IMPROVING EXPORT AND IMPORT OPERATIONS: ANALYSIS AND AUDIT - Misirov Asliddin Mamasobirovich (Ecominds Press, 2026)
This article examines modern methods of analysis and audit of export and import operations in the development of foreign economic activity. Also, issues of optimization of international trade turnover, audit of customs fees and risk management were analyzed in depth.
Keywords: World, subsidy, statistics, import, export, efficient, economic activity, criteria, raw materials, balance, digital, technology.